Bathymetric characteristics in the Krueng Raba Lhok Nga and Krueng Leupung, Aceh Besar Regency, Indonesia - Setiawan Ichsan; Yuni Syarifah Meurah; Maulana Febri; Muttaqin Ichlasul; Rizwan Thaib (BIO Web of Conferences)
Depth information is a very important aspect for several studies of marine resource activities, both deep water and shallow water depths. Information on bathymetry is needed, especially in areas that have tourism potential such as waters in river basins that can be used as fishing areas, pond cultivation, and tourism areas. The purpose of this study was to determine the depth of the Krueng Raba and Krueng Leupung watersheds. This study used a conventional method by lowering lead weights to the bottom of the waters and then measuring them using a roll meter. Based on the results of the study, the bathymetry of the Krueng Raba watershed ranges from 0.95 m to 5.58 m, and Krueng Leupung ranges from 0.88 m to 4.10 m. The findings of variations in the watershed bathymetry are influenced by the morphology of the river and the surrounding land.